Are dairy farmers willing to pay for improved forage varieties? Experimental evidence from Kenya - Osiemo, Jamleck; Sibiko, Kenneth Waluse; Ng Ang A, Stanley Karanja; Notenbaert, An Maria Omer (Elsevier, 2024)
Though improved forage varieties have the potential to supply high quality feed for livestock and optimize livestock nutrition and production, demand for them in developing countries is low. To inform interventions aiming to increase demand for the improved forages such as pricing, we assessed farmers’ willingness to pay (WTP) for different improved seeds and two types of dried feed in Meru County Kenya. We used a mix of sampling strategies to recruit 356 dairy farmers into the study. We used the Becker-De-Groote Marschak (BDM) mechanism to elicit WTP, and a mixed effects model in the analysis. We find that the WTP for the forage products (except one) was below the market prices, and that the WTP differed significantly between farmers in cooperatives and those that were not. For related varieties, none is significantly superior to other varieties in terms of WTP. We also find that farmers who had prior exposure to the forages, larger farm sizes, mainly practiced zero grazing, and owned the livestock were more likely to bid above the market prices. Our results underscore the need for strategies that can lower the prices of the improved forages such as reducing the costs associated with their production, certification, storage, and transportation. Training farmers especially on the benefits of the improved traits can potentially increase the likelihood of farmers paying premiums for the improved traits, an important ingredient for the commercialization of the improved forage products at scale.